The association between unexpected weight loss and cancer diagnosis in primary care: a matched cohort analysis of 65,000 presentations - Nicholson, BD; Hamilton, W; Koshiaris, C; Oke, JL; Hobbs, FDR; Aveyard, P (Springer Nature, 2020)
BACKGROUND:We aimed to understand the time period of cancer diagnosis and the cancer types detected in primary care patients with unexpected weight loss (UWL) to inform cancer guidelines. METHODS:This retrospective matched cohort study used cancer registry linked electronic health records from the UK's Clinical Practice Research Datalink from between 2000 and 2014. Univariable and multivariable time-to-event analyses examined the association between UWL, and all cancers combined, cancer site and stage. RESULTS:In all, 63,973 patients had UWL recorded, of whom 1375 (2.2%) were diagnosed with cancer within 2 years (days-to-diagnosis: mean 181; median 80). Men with UWL (HR 3.28 (2.88-3.73)) and women (1.87 (1.68-2.08)) were more likely than comparators to be diagnosed with cancer within 3 months. The association was greatest in men aged ≥50 years and women ≥70 years. The commonest cancers were pancreas, cancer of unknown primary, gastro-oesophageal, lymphoma, hepatobiliary, lung, bowel and renal-tract. The majority were late-stage, but there was some evidence of association with stage II and stage III cancers. In the 3-24 months after presenting with UWL, cancer diagnosis was less likely than in comparators. CONCLUSION:UWL recorded in primary care is associated with a broad range of cancer sites of early and late-stage.